IgG antiglobulins in rheumatoid arthritis and other arthritides: relationship with clinical features and other parameters. Issue 2 (April 1981) - Allen, C; Elson, C J; Scott, D G; Bacon, P A; Bucknall, R C
Abstract : A radioimmunoassay has been developed for measuring IgG antiglobulins using baboon IgG as antigen. Raised levels were virtually confined to the sera of patients with rheumatoid arthritis (RA) and not found in other seronegative arthritides. High levels were found in both seropositive and seronegative (as judged by latex slide and sheep cell differential agglutination for IgM antiglobulins) patients with RA and were associated with systemic disease but not synovitis. Very high levels (more than twice the upper limit of normal) showed a strong association with vasculitis.